2020
DOI: 10.1080/13575279.2020.1805988
|View full text |Cite
|
Sign up to set email alerts
|

Communities as Enablers: Broadening our Thinking on Core Components of Youth Resilience

Abstract: Several decades of resilience research with children and youth at risk of poor psychosocial outcomes has demonstrated that resilience is an interactive process that draws on both the characteristics of the individual as well as relational and physical resources located in the environment, to support better-than-expected-outcomes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…First, scholars have focused on social resilience, or the “capacity of groups of people to sustain and advance their wellbeing in the face of challenges” ( Hall and Lamont, 2013 :2). This work examines how actors respond to crises by mobilizing cultural, institutional, and social resources (e.g., Bourbeau, 2018 ; Liebenberg et al, 2020 ; Obrist et al, 2010 ; Schoon, 2006 ; Tierney, 2015 ). For example, Ungar (2004) defines resilience as the “outcome from negotiations between individuals and their environments for the resources to define themselves as healthy amidst conditions collectively viewed as adverse” (342).…”
Section: Social Resilience As a Temporally-embedded Processmentioning
confidence: 99%
“…First, scholars have focused on social resilience, or the “capacity of groups of people to sustain and advance their wellbeing in the face of challenges” ( Hall and Lamont, 2013 :2). This work examines how actors respond to crises by mobilizing cultural, institutional, and social resources (e.g., Bourbeau, 2018 ; Liebenberg et al, 2020 ; Obrist et al, 2010 ; Schoon, 2006 ; Tierney, 2015 ). For example, Ungar (2004) defines resilience as the “outcome from negotiations between individuals and their environments for the resources to define themselves as healthy amidst conditions collectively viewed as adverse” (342).…”
Section: Social Resilience As a Temporally-embedded Processmentioning
confidence: 99%
“…Autori koji otpornost poimaju kao crtu ličnosti izjedna-One of the important intrapersonal/internal protective factors is resiliency, which refers to a set of personality traits that reflect the general resourcefulness of a person, strength of their character, and flexibility in responding to adversity (Block andBlock, 1980, according to Luthar et al, 2000), i.e., competence to adapt to and recover from adversity (Prince-Embury, Saklofske and Veseley, 2015). It must be mentioned that researchers who considered resilience as a personality trait equated the term resiliency with resilience, but the dominant view in the literature is that the two terms should be considered separately because it has been found that resilience cannot be a personality trait because resources in the environment can play an even greater role in coping with adversity than individual resources (Liebenberg VanderPlaat and Dolan, 2020). Resiliency is positively associated with life satisfaction (Beutel, Glaesmer, Decker, Fischbeck and Brähler, 2009;Lau, Feher, Wilson, Babcock and Saklofske, 2018) and has been shown to reduce the negative effects associated with ACE by strengthening the mechanisms of coping with stress, emotional intelligence, and overall functioning (Flynn, Parnes and Conner, 2021).…”
Section: Introductionmentioning
confidence: 99%